Implementasi Program Pembedayaan Nelayan Tradisional Di Pulau-Pulau Kecil Morotai Tahun 2023 - Sumai, Saiful (Peneliti.net, 2025)
The implementation of the traditional fishermen empowerment program on the small islands of Morotai is the implementation of the program of the Marine and Fisheries Service of Morotai Island Regency which is contained in the 2023-2026 marine and fisheries development strategy plan. The implementation of traditional fishermen empowerment programs is directed at improving the welfare of coastal communities and small islands, also intended to realize increased productivity and quality of capture and aquaculture resources, boost investment added value, create economic competitiveness and create job opportunities. The location of this study is in DKP Morotai Island, Koloray Island, Galo-Galo and Ngele-Ngle. This study used a qualitative descriptive approach with data collection techniques through observation, interviews, documentation studies with informant determination through purposive sampling and snowball sampling. The theory used is the implementation model of Goerge C. Edward III. The results showed that the implementation of the empowerment program for traditional fishing groups on the small islands of Morotai refers to theoretical variables, this empowerment program has not been maximized due to (1) lack of budget; seen in budget political policies that have not fully met the interests of the target group of empowerment; (2) inadequate carrying capacity of human resources; It can be seen that the development of business systems that are still traditional in nature affects the productivity of the utilization of aquatic resources in conservation area zones.